Association of dietary inflammatory index and refractive status in American adolescents: NHANES 1999–2008 - Chen, Xiaodong; Li, Xuewei; Xu, Ningda; Li, Jiarui; Guo, Qianwen; Miao, Heng; Wang, Kai; Huang, Lvzhen (Frontiers in Medicine, 2024)
Background Several nutrients have been found to be associated with the prevalence of myopia, and the role of dietary patterns in influencing myopia risk has recently garnered significant attention. We aim to explore the relationship between the Dietary Inflammatory Index (DII) and refractive status in adolescents. Methods Data from 7,331 participants were analyzed from the 2005–2008 US National Health and Nutrition Examination Survey (NHANES). Smooth curve fitting and linear regression analysis were used to explore both non-linear and linear relationships between DII and spherical equivalent refraction (SER). The threshold effect of DII on SER was analyzed using a two-piecewise linear regression model. Results DII was connected with a lower SER, indicating a shift toward myopia (β: –0.0586; 95% CI: −0.1109 to −0.0063; p < 0.05). Compared to the first quartile, the third quartile (β: –0.2512; 95% CI: −0.4952 to −0.0072; p < 0.05) and the fourth quartile (β: –0.2905; 95% CI: −0.5030 to −0.0780; p < 0.01) were significantly associated with a lower SER. Smooth curve fitting revealed a non-linear relationship between DII and SER, with a turning point at 0.81. For DII values below 0.81, there was no significant association with SER (β: –0.0450; 95% CI: −0.0272 to −0.1173; p > 0.05). However, for DII values ≥0.81, a significant association with lower SER was observed (β: –0.1197; 95% CI: −1.1722 to −0.0672; p < 0.01). Conclusion These findings indicate that a higher DII (≥0.81) may contribute to the progression of myopia. This study highlights the potential for dietary recommendations in myopia prevention. Prospective studies are required to validate these findings and establish causal relationships.